Misconceiving patient reported outcome measures (PROMs) as primarily a reporting requirement rather than a quality improvement tool: perceptions of independent healthcare sector stakeholders in the UK - Michael Anderson; Emma Pitchforth; Andrew Vallance-Owen; Elias Mossialos; Paul Millner; Jon Fistein (SpringerOpen, 2022)
Abstract Background The independent healthcare sector in the UK collects PROMs for several surgical procedures, but implementation has been challenging. We aimed to understand the enablers and barriers to PROMs implementation in the independent healthcare sector in the UK. Method Between January and May 2021, we remotely conducted semi-structured interviews with hospital consultants, hospital managers and other clinical staff using a topic guide developed from an implementation science framework called the Theoretical Domains Framework (TDF). Results We interviewed 6 hospital consultants, 5 hospital managers, and 3 other clinical staff (1 nurse and 2 physiotherapists) across 8 hospitals. Common barriers included: the perception that PROMs are predominantly a reporting requirement rather than a quality improvement tool, absence of feedback mechanisms for PROMs data for clinicians, poor awareness of PROMs among healthcare professionals and the public, absence of direction or commitment from leadership, and limited support from hospital consultants. Common enablers included: regular feedback of PROMs data to clinicians, designating roles and responsibilities, formally embedding PROMs collection into patient pathways, and involvement of hospital consultants in developing strategies to improve PROMs uptake. Conclusion To support PROMs implementation, independent hospitals need to develop long-term organisational strategies that involve sustained leadership commitment, goals or targets, training opportunities to staff, and regular feedback of PROMs data at clinical or governance meetings. The primary purpose of PROMs needs to be reframed to independent healthcare sector stakeholders as a quality improvement tool rather than a reporting requirement.